Multiband adjustment engineering strategy for broadband range in photonic crystals - Wenjia Yu; Shiyu Liu; Hang Sun; Jicheng Wang; Yuting Yang; Xiaopeng Shen (Results in Physics)
Topological edge states are crucial for optical modulation, and the overlapping Brillouin zones in nested structures can effectively control multiband edge states. A nested photonic crystal framework can enhance the rotational freedom, providing additional functionalities. In this study, a multifunctional, tunable, innovative double-rotation C4 nested photonic crystal structure was developed; it reached a higher degree of freedom via double independent rotations. These nested C4 photonic crystal structures could expand the functional range of C4 structure implementation. The multifunctional implementation of multienergy band transmissions, unidirectional transmissions, and wavelength division multiplexers containing nested C4 structures were experimentally demonstrated. The experimental results agreed well with the simulated predictions. Thus, this study offers new insights and strategies to foster the advancement of topological photonics and radar communication devices.